2016
DOI: 10.1007/jhep01(2016)087
|View full text |Cite
|
Sign up to set email alerts
|

Fermionic semi-annihilating dark matter

Abstract: Semi-annihilation is a generic feature of dark matter theories with symmetries larger than Z 2 . We investigate two examples with multi-component dark sectors comprised of an SU (2) L singlet or triplet fermion besides a scalar singlet. These are respectively the minimal fermionic semi-annihilating model, and the minimal case for a gauge-charged fermion. We study the relevant dark matter phenomenology, including the interplay of semi-annihilation and the Sommerfeld effect. We demonstrate that semi-annihilation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 133 publications
(175 reference statements)
0
29
0
Order By: Relevance
“…This can allow strong indirect signals while weakening other constraints. In a previous work [45], we showed that SA in a two-component DM model could explain the GCE through processes where a single Higgs is produced nearly at rest. 1 The subsequent decay of the Higgs to bb produces a spectrum very similar to annihilation of 60 GeV DM to the same final state.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This can allow strong indirect signals while weakening other constraints. In a previous work [45], we showed that SA in a two-component DM model could explain the GCE through processes where a single Higgs is produced nearly at rest. 1 The subsequent decay of the Higgs to bb produces a spectrum very similar to annihilation of 60 GeV DM to the same final state.…”
Section: Introductionmentioning
confidence: 89%
“…Collider searches in monojets and jets + MET set no current bounds in the mass range of interest, and are not expected to be constraining in the near future [45,67,68].…”
Section: Jhep06(2016)156 4 Additional Constraintsmentioning
confidence: 99%
“…Our model is a simple extension of the SM by including a Dirac fermion χ and two real scalars S and φ. We firstly impose the following stabilizing symmetry on the model [72]:…”
Section: The Modelmentioning
confidence: 99%
“…Since we assume S = 0, the stabilizing symmetry remains unbroken. Note also that the above Lagrangian is invariant under its subgroup of this symmetry: χ → −χ [72]. Therefore, when mass of the scalar S is below half of the Dirac fermion χ mass, both particles are stable and can contribute to the final DM relic density.…”
Section: The Modelmentioning
confidence: 99%
“…More interestingly, as pointed out in refs. [108,109], singlet models with a global Z 3 symmetry can also fit the GCE signal when taking into account SE-A contributions properly. In such models, DM candidates can be either a scalar or a two-component scalar and fermion.…”
Section: Comment On Gamma-ray Excess From the Galactic Centermentioning
confidence: 99%